diff --git a/tests/rbf_interpolation.h b/tests/rbf_interpolation.h index 8da6721a..15fa2946 100644 --- a/tests/rbf_interpolation.h +++ b/tests/rbf_interpolation.h @@ -49,37 +49,39 @@ Here we interpolate a function $f(x,y)$ over the two-dimensional unit cube from The function to be interpolated is \begin{equation} -f(x,y) = \exp(-9(x-\frac{1}{2})^2 - 9(y-\frac{1}{4})^2) +f(x,y) = \exp(-9(x-\frac{1}{2})^2 - 9(y-\frac{1}{4})^2), \end{equation} and the multiquadric RBF $K(r)$ is given by \begin{equation} -K(r) = \sqrt{r^2 + c^2} +K(r) = \sqrt{r^2 + c^2}. \end{equation} -We create a set of basis functions around a set of $N$ particles with positions $\mathbf{x}_i$. In this case the radial coordinate around each point is $r = ||\mathbf{x}_i - \mathbf{x}||$. The function $f$ is approximated using the sum of these basis functions, with the addition of a constant factor $\alpha$ +We create a set of basis functions around a set of $N$ particles with positions $\mathbf{x}_i$. In this case the radial coordinate around each point is $r = ||\mathbf{x}_i - \mathbf{x}||$. The function $f$ is approximated using the sum of these basis functions, with the addition of a constant factor $\beta$ \begin{equation} -f_i(\mathbf{x}) = \beta + \sum_j \alpha_j K(||\mathbf{x}_j-\mathbf{x}||) +\overline{f}(\mathbf{x}) = \beta + \sum_i \alpha_j K(||\mathbf{x}_i-\mathbf{x}||). \end{equation} -We exactly interpolate the function at $\mathbf{x}_i$ (i.e. set $f_i(\mathbf{x}_i)=f(\mathbf{x}_i)$), leading to +We exactly interpolate the function at $\mathbf{x}_i$ (i.e. set $\overline{f}(\mathbf{x}_i)=f(\mathbf{x}_i)$), leading to \begin{equation} -f(\mathbf{x}_i) = \beta + \sum_j \alpha_j K(||\mathbf{x}_j-\mathbf{x}_i||) +f(\mathbf{x}_i) = \beta + \sum_j \alpha_j K(||\mathbf{x}_j-\mathbf{x}_i||). \end{equation} -with the additional constraint +Note that the sum $j$ is over the same particle set. + +We also need one additional constraint to find $\beta$ \begin{equation} -0 = \sum_j \alpha_j +0 = \sum_j \alpha_j. \end{equation} -which can be written as a linear algebra expression +We rewrite the two previous equations as a linear algebra expression \begin{equation} -\mathbf{\Phi} = \begin{bmatrix} \mathbf{G}&\mathbf{P} \\\\ \mathbf{P}^T & \mathbf{0} \end{bmatrix} \begin{bmatrix} \mathbf{\alpha} \\\\ \mathbf{\beta} \end{bmatrix} = \mathbf{H} \mathbf{\gamma} +\mathbf{\Phi} = \begin{bmatrix} \mathbf{G}&\mathbf{P} \\\\ \mathbf{P}^T & \mathbf{0} \end{bmatrix} \begin{bmatrix} \mathbf{\alpha} \\\\ \mathbf{\beta} \end{bmatrix} = \mathbf{W} \mathbf{\gamma}, \end{equation} where $\mathbf{\Phi} = [f(\mathbf{x}_1),f(\mathbf{x}_2),...,f(\mathbf{x}_N),0]$, $\mathbf{G}$ is an $N \times N$ matrix with elements $G_{ij} = K(||\mathbf{x}_j-\mathbf{x}_i||)$ and $\mathbf{P}$ is a $N \times 1$ vector of ones.